How is equity approached in universal health coverage? An analysis of global and country policy documents in Benin and Senegal - Elisabeth Paul; Céline Deville; Oriane Bodson; N'koué Emmanuel Sambiéni; Ibrahima Thiam; Marc Bourgeois; Valéry Ridde; Fabienne Fecher (BMC, 2019)
Abstract Background Equity seems inherent to the pursuance of universal health coverage (UHC), but it is not a natural consequence of it. We explore how the multidimensional concept of equity has been approached in key global UHC policy documents, as well as in country-level UHC policies. Methods We analysed a purposeful sample of UHC reports and policy documents both at global level and in two Western African countries (Benin and Senegal). We manually searched each document for its use and discussion of equity and related terms. The content was summarised and thematically analysed, in order to comprehend how these concepts were understood in the documents. We distinguished between the level at which inequity takes place and the origin or types of inequities. Results Most of the documents analysed do not define equity in the first place, and speak about "health inequities" in the broad sense, without mentioning the dimension or type of inequity considered. Some dimensions of equity are ambiguous - especially coverage and financing. Many documents assimilate equity to an overall objective or guiding principle closely associated to UHC. The concept of equity is also often linked to other concepts and values (social justice, inclusion, solidarity, human rights - but also to efficiency and sustainability). Regarding the levels of equity most often considered, access (availability, coverage, provision) is the most often quoted dimension, followed by financial protection. Regarding the types of equity considered, those most referred to are socio-economic, geographic, and gender-based disparities. In Benin and Senegal, geographic inequities are mostly pinpointed by UHC policy documents, but concrete interventions mostly target the poor. Overall, the UHC policy of both countries are quite similar in terms of their approach to equity. Conclusions While equity is widely referred to in global and country-specific UHC policy documents, its multiple dimensions results in a rather rhetorical utilisation of the concept. Whereas equity covers various levels and types, many global UHC documents fail to define it properly and to comprehend the breadth of the concept. Consequently, perhaps, country-specific policy documents also use equity as a rhetoric principle, without sufficient consideration for concrete ways for implementation.